COLOR HARMONY IN FINE ARTS AND ITS PSYCHOLOGICAL EFFECTS (Web of Teachers: Inderscience Research, 2025)
The role of colors in the expression of the most subtle and complex aspects of the human spirit of Fine Art is incomparable. Through colors, artists express their feelings, thoughts and worldviews, deeply affecting the viewer's heart. Color harmony, on the other hand, is the primary means of this expression process. The harmony, harmony and contrast of colors create the aesthetic beauty of a work of Art, give it a soul and enhance its psychological impact. Color harmony is not only the juxtaposition of colors, but also their influence on the human mind, emotions and psyche. For this reason, a deep understanding of color harmony is one of the most important aspects of visual art.